Evaluation of Kratom Opioid Derivatives as Potential Treatment Option for Alcohol Use Disorder - Gutridge, Anna M.; Chakraborty, Soumen; Varga, Balazs R.; Rhoda, Elizabeth S.; French, Alexander R.; Blaine, Arryn T.; Royer, Quinten H.; Cui, Haoyue; Yuan, Jinling; Cassell, Robert J.; Szabó, Márk; Majumdar, Susruta; et al. (Frontiers in Pharmacology, 2021)
Background and Purpose: Mitragyna speciosa extract and kratom alkaloids decrease alcohol consumption in mice at least in part through actions at the δ-opioid receptor (δOR). However, the most potent opioidergic kratom alkaloid, 7-hydroxymitragynine, exhibits rewarding properties and hyperlocomotion presumably due to preferred affinity for the mu opioid receptor (µOR). We hypothesized that opioidergic kratom alkaloids like paynantheine and speciogynine with reduced µOR potency could provide a starting point for developing opioids with an improved therapeutic window to treat alcohol use disorder. Experimental Approach: We characterized paynantheine, speciociliatine and four novel kratom-derived analogs for their ability to bind and activate the δOR, µOR and κOR. Select opioids were assessed in behavioral assays in male C57BL/6N WT and δOR knockout mice. Key Results: Paynantheine (10 mg∙kg-1, i.p.) produced aversion in a limited conditioned place preference (CPP) paradigm but did not produce CPP with additional conditioning sessions. Paynantheine did not produce robust antinociception but did block morphine-induced antinociception and hyperlocomotion. Yet, at 10 and 30 mg∙kg 1 doses (i.p.), paynantheine did not counteract morphine CPP. 7-hydroxypaynantheine and 7-hydroxyspeciogynine displayed potency at δOR but limited µOR potency relative to 7-hydroxymitragynine in vitro, and dose-dependently decreased voluntary alcohol consumption in WT but not δOR KO mice. 7 hydroxyspeciogynine has a maximally tolerated dose of at least 10 mg∙kg-1 (s.c.), at which it did not produce significant CPP, alter general locomotion, nor induce noticeable seizures. Conclusion and Implications: Derivatizing kratom alkaloids with the goal of enhancing δOR potency and reducing off-target effects could provide a pathway to develop novel lead compounds to treat alcohol use disorder with improved therapeutic window.